PENINGKATAN KEMAMPUAN SISWA SMAN 8 DENPASAR DALAM MENYELESAIKAN SOAL CERITA POKOK BAHASAN PROGRAM LINIER MATA PELAJARAN MATEMATIKA - Asih, I M. (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Volume 10 No.2 – September 2011, 2012)
This community service was conducted on 1 - 30 August 2010, at SMAN 8 Denpasar, with 36 students of grade XII as the participants of this activity. It aims to improve the understanding of student about the ways to solve word problems of linear programming as correctly and concept along with its steps, and also to know the level of student mastery in solving word problems of linear programming subject, mathematics courses. Problem solving method was taken in the form of learning activities for linear programming for high school students in grade XII conducted by the implementing activities jointly with the classroom teacher. The results of the analysis scores pre test and post test showed that the learning provided during this activity, an increase in the percentage of students’ mastery of subject matter about the material word problems of linear programming by an average of 57.83%. The results of cross tabulation analysis between the pre test and post test indicate that a given learning can enhance students’ mastery of the material word problems linear programming, from which initially less become category of enough and good, from enough become good and excellent, and from category of good become excellent. T test results obtained t value of -9.595 with a probability of 0.000. Means that a given learning provides a significant improvement of students’ mastery of the subjects completed the word problems linear programming mathematics course.